2007
DOI: 10.1158/0008-5472.can-06-4093
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Starvation Induces Differentiation of Human Leukemia HL-60 Cells

Abstract: Cholesterol metabolism is particularly active in malignant, proliferative cells, whereas cholesterol starvation has been shown to inhibit cell proliferation. Inhibition of enzymes involved in cholesterol biosynthesis at steps before the formation of 7-dehydrocholesterol has been shown to selectively affect cell cycle progression from G 2 phase in human promyelocytic HL-60 cells. In the present work, we explored whether cholesterol starvation by culture in cholesterol-free medium and treatment with different di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…In contrast to a meta-analysis of cohort studies 24 , we found no association between BMI and AML. Our findings of an inverse association between cholesterol and myeloid neoplasms in particular AML is consistent with results from experimental studies 25,26 . Reverse causation is thought to contribute to the inverse association 27 since time-dependent associations have been reported between cholesterol and cancer risk 28 .…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to a meta-analysis of cohort studies 24 , we found no association between BMI and AML. Our findings of an inverse association between cholesterol and myeloid neoplasms in particular AML is consistent with results from experimental studies 25,26 . Reverse causation is thought to contribute to the inverse association 27 since time-dependent associations have been reported between cholesterol and cancer risk 28 .…”
Section: Discussionsupporting
confidence: 91%
“…The hypothesis of cholesterol synthesis involvement in the self‐renewal/differentiation balance is in agreement with previous studies pointing out a link between cholesterol homeostasis and differentiation. First, it was shown that both HMG‐CoA reductase inhibition (31) and, more specifically, cholesterol starvation (32) induce differentiation of human leukaemia HL‐60 cells. Moreover, hypercholesterolaemia has been reported to result in blockage of erythroid differentiation (33).…”
Section: Discussionmentioning
confidence: 99%
“…To meet these needs, these deregulated cells are able to promote two strategies cholesterol uptake from the bloodstream and de novo cholesterol biosynthesis 14 . In this context, hypercholesterolemia has been identified as a risk factor in the development or malignant drift of some solid tumors, such as in breast, colon, and prostate cancer 58 . In contrast, the inhibition of the cholesterol synthesis pathway can activate the mechanisms of cell differentiation 9 .…”
Section: Introductionmentioning
confidence: 99%